Sperm Motility, Bronchiectasis, Sinusitis and the Diagnosis of Primary Ciliary Dyskinesia - Guevara Pineda, Marí Luisa (1999)
OBJETIVES: To evaluate the association between immotile sperms and the history of bronchiectasis and sinusitis, in order to identify a common cilliary structural abnormality. MATHERIAL AND METHODS: Seventeen subjects (mean age: 23 years), with history of bronchiectasis and sinusitis underwent a spermatogram, searching for immotility of sperm. RESULTS: Ten patients (58,85%) had sperm immotility, one of which was azospermic. They had had chronic respiratory infections, as well as diffuse bronchiectasis. On the other hand, patients with preserved motility of the sperm presented mainly acute respiratory events. CONCLUSIONS: The structural abnormality leading to impaired motility of respiratory cilia, which results in frequent respiratory events, can be associated with the immotility of the sperm cilia, since human cilia structure is the same.